2020
DOI: 10.1177/1096348020919990
|View full text |Cite
|
Sign up to set email alerts
|

Scenario Forecasting for Global Tourism

Abstract: This study provides innovative forecasts of the probabilities of certain scenarios of tourism demand. The scenarios of interest are constructed in relation to tourism growth and economic growth. The probability forecasts based on these scenarios provide valuable information for destination policy makers. The time-varying parameter panel vector autoregressive (TVP-PVAR) model is adopted for scenario forecasting. Both the accuracy rate and the Brier score are used to evaluate the forecasting performance. A globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 58 publications
(85 reference statements)
1
12
0
Order By: Relevance
“…Overall, these initial attempts to forecast tourism recovery after the pandemic indicate the value of judgmental assessment and scenario forecasting in a context of high uncertainty and in line with other studies (Wu et al, 2020) highlight the value that this type of modeling can bring to policy makers. Moreover, the studies clearly indicate that more detailed information and accurate data would be essential to improve the models and provide greater value to decision makers.…”
Section: Tourism Forecasting Models Amid Health Crisessupporting
confidence: 78%
See 1 more Smart Citation
“…Overall, these initial attempts to forecast tourism recovery after the pandemic indicate the value of judgmental assessment and scenario forecasting in a context of high uncertainty and in line with other studies (Wu et al, 2020) highlight the value that this type of modeling can bring to policy makers. Moreover, the studies clearly indicate that more detailed information and accurate data would be essential to improve the models and provide greater value to decision makers.…”
Section: Tourism Forecasting Models Amid Health Crisessupporting
confidence: 78%
“…In the case of no protective effect of the currently available vaccinations, the high likelihood of the "COVID new wave" scenario would increase with the disastrous effects forecasted in this proposed analysis. According to Wu et al (2020), scenario forecasting modeling can be divided into two main types: (1) a modeling approach that forecasts tourism demand given certain conditions or scenarios; and (2) the other approach that aims to predict the probability of a given scenario or condition. This research focuses on the first type.…”
Section: Discussionmentioning
confidence: 99%
“…Single forecasting mainly includes three types. The first is regression analysis based on statistics, and the representatives are VAR ( Wu, Cao, Wen, & Song, 2021 ) and ARMA family, i.e., ARIMA ( Jin et al, 2019 ), SARIMA ( Qiu et al, 2021 ), ARIMAX ( Hu, Qiu, Wu, & Song, 2021 ), and SARIMAX ( Song, Qiu, & Park, 2019 ; Wu, Song, & Shen, 2017 ). They are of better adaptability to linear data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…independent variables), some studies have shown that a series of economic indicators including the destination's tourism prices, tourism prices of competitive destinations, tourist income and exchange rates are the most important factors affecting tourism demand (Song and Li, 2008). The most commonly used econometric models to analyze the causal relationship between tourism demand and its influencing factors include the autoregressive distributed lag (hereinafter, ARDL) model (Song et al, 2012), the error-correction model (hereinafter, ECM) (Goh, 2012), the vector autoregressive (VAR) model (Witt et al, 2004) and the time-varying parameter (hereinafter, TVP) model (Li et al, 2006;Wu et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%